Effectiveness of two treatments to promote tree regeneration: implications for forest restoration in the Isla del Coco National Park, Costa Rica - Acosta-Vargas, Luis; Rovere, Adriana E.; Camacho-Sandoval, Jorge (Revista de Biología Tropical, 2020)
Introduction: Isla del Coco is the only island in the Eastern Tropical Pacific with humid tropical forests; 296 plant species are reported, of them, 22% are endemic. Their ecology is poorly understood. Deforestation and the introduction of rats, feral pigs and white-tailed deer are the primary agents of forest degradation. After more than 120 years, the deforested areas have never recovered the native forest. Objective: To analyse if the deforested area keeps its resilience, we evaluated the natural regeneration and ecological processes associated. Methods: From August 2016 to June 2018, we conducted a restoration experiment consisting of a randomized complete blocks design including vegetation cutting, vegetation uprooting and controls as treatments. Plots were protected with an exclusion fence to avoid herbivores. Results: There were no differences between plant cutting and uprooting in stimulating natural regeneration. We only recorded the seedlings of two tree species, 35 individuals of Cecropia pittieri and three of Sacoglottis holdridgei, both endemic. Their regeneration established during the first 15 months mainly. At the end of the experiment, the structure and composition of the vegetation changed from bushes dominated by Entada gigas (28%) and Clidemia strigillosa (12%) to grasses dominated by Paspalum conjugatum (39%). Entada gigas has a high recolonizing potential with a growing rate of 1.6±0.2m/month. Conclusions: As filters for restoration we determined herbivores, which pose a strong negative impact in the development of the forest; the exhausted seed bank of tree species and scarce or null seed dispersion.